The new peace linguistics and the role of language in conflict - Curtis, Andy (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"The idea of Peace Linguistics (PL) has been around for decades. However, the practice of PL has only occurred much more recently, only within the last few years, since the first credit-bearing, university-level PL course was taught at Brigham Young University-Hawaii in 2017. Since then, the field of NPL has grown beyond its original goals, of using peaceful language and language that avoids or de-escalates conflict. The New Peace Linguistics (NPL) focuses on in-depth, systematic analyses of the spoken and written language of some of the most powerful people in the world, such as presidents of the USA, as it is they who have the power to start wars or to bring peace. As the first book to be published on PL and on NPL, this work represents a ground-breaking study of the power of language to hurt and harm or to help and give hope. The first four chapters of the book, which provide the foundation on which the rest of the book is built, introduce the concept of Peace Linguistics (PL) and the New Peace Linguistics, starting with the origins of PL and coming to the present day. The remaining Part Two and Part Three chapters present in-depth, systematic NPL analyses of George W. Bush, Colin L. Powell, Barack H. Obama, Donald J. Trump and Joseph R. Biden. The concluding chapter reiterates the most important distinguishing and recurring features of NPL, and looks at where the field may be headed in the future"-- Provided by publisher.
Keywords: Language and peace.; Language and languages -- Political aspects.; Rhetoric -- Political aspects.; Communication -- Political aspects.; Political Science -- Peace.; Peace studies and conflict resolution.; elektronické knihy; electronic books